†Kinzelbachilla ellenbergeri – a new ancestral species, genus and family of Strepsiptera (Insecta). (January 2016) - POHL, HANS; BEUTEL, ROLF G.
Abstract: A single male specimen of a new species († Kinzelbachilla ellenbergeri gen. et sp.n. ) of a new family of the endoparasitic Strepsiptera (†Kinzelbachillidaefam.n.) from Burmese amber is described and evaluated with respect to its systematic placement. Its features come very close to the presumptive groundplan of the order suggested in recent studies. Preserved plesiomorphic features are the following: fully sclerotized head with long coronal suture, small ommatidia not separated by chitinous bridges, absence of microtrichia between ommatidia, eight antennomeres, robust mandibles with dicondylic articulation, galea distinctly developed, free pro‐ and mesotrochanters, slender five‐segmented tarsi without adhesive soles, and equally sclerotized abdominal tergites and sternites. An important character that is not recognizable due to damage is the shape of the metapostnotum. This structure is transverse in the groundplan of Strepsiptera and in † Protoxenos, but elongated and shield‐like in all other known strepsipterans. In a cladistic analyses of 82 characters of adult males and additional characters for females and immatures (scored as unknown for all included fossils) † Kinzelbachilla is placed as sister group of all remaining strepsipterans except for † Protoxenos, followed by † Cretostylops and † Mengea as the third and fourth branches in the stem group, respectively. The position of † Protoxenos as first branch is suggested by three unambiguous apomorphic features of all remaining Strepsiptera, the reduced size of less than 6 mm, mandibles distinctly narrowing distad the basalmost part, and fan‐shaped hindwings which are broader than they are long. The hitherto known fossil stem group strepsipterans do not distinctly narrow the large morphological gap separating this order from its sister group, the Coleoptera. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:07554C01-DEC3-4080-A337-B1F46BC9070F .